Product and mould design for motorcycle stand using CAD technique / Sayuti Nashir and Abdul Wapi Hashim - Nashir, Sayuti; Hashim, Abdul Wapi (2002)
Nowadays an auto CAD system becomes a powerful tool to develop and enhance manufacturing design efficiency , particularly in plastic automotive and others metal part industries. By using this system , designer will be able to conduct an analysis in CAE subsequently after completing their design in CAD to determine whether the design is free from errors before the CAM work can take place. In this project, the main objective is to evaluate the effectiveness of CAD system. For the purpose of design, AutoCAD software was used for the CAD system. Through this , we were able to demonstrate the capabilities of CAD system, which can be used directly in design practice. The important gain of this project is to understand the CAD system, which lead to benefit, especially in design, engineering and manufacturing productivity processes.